2020
DOI: 10.1038/s41598-020-76789-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential parameters between activity flare and acute infection in pediatric patients with systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) patients are vulnerable to infections. We aim to explore the approach to differentiate active infection from disease activity in pediatric SLE patients. Fifty pediatric SLE patients presenting with 185 clinical visits were collected. The associations between both clinical and laboratory parameters and the outcome groups were analyzed using generalized estimating equations (GEEs). These 185 visits were divided into 4 outcome groups: infected-active (n = 102), infected-inactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The role of CRP in clinical disease activity in SLE is still complex and controversial; some studies reported that CRP levels are normal or only modestly elevated in active SLE and that there is no relationship between CRP levels and clinical disease activity [ 12 , 13 ]. In contrast, we found that patients with active SLE had higher CRP levels than inactive SLE patients; additionally, we observed a positive correlation between Mex-SLEDAI score and CRP levels when we adjusted for some variables that could influence it, such as age, fat mass, and BMI [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of CRP in clinical disease activity in SLE is still complex and controversial; some studies reported that CRP levels are normal or only modestly elevated in active SLE and that there is no relationship between CRP levels and clinical disease activity [ 12 , 13 ]. In contrast, we found that patients with active SLE had higher CRP levels than inactive SLE patients; additionally, we observed a positive correlation between Mex-SLEDAI score and CRP levels when we adjusted for some variables that could influence it, such as age, fat mass, and BMI [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CRP’s role in active SLE is still complex and controversial, some studies have reported that CRP levels are normal or modestly elevated in active SLE, and that there is no relationship between CRP levels and clinical disease activity [ 12 , 13 ]. Nevertheless, it is widely described that in active SLE patients there is an increase in inflammatory cytokines such as IL-6, which could directly drive the CRP serum levels, suggesting a potential relationship between the increase in IL-6 in the active SLE and higher CRP serum levels [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present case had triggered a controversy on whether the pyomyositis and osteomyelitis was a genuine infection or the SLE disease activity. There are many biomarkers associated with the infection as well as for SLE disease (non-infection inflammation), such as C-reactive protein, procalcitonin level, leukocyte count, complement levels, anti-dsDNA, and Systemic Lupus Erythematosus Disease Activity Index score [ 31 33 ]. Among those, C-reactive protein was shown as a potent marker to diagnose infection in patients with SLE [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These exclusion criterion eliminate confounding factors that could have affected the study outcomes. Any episodes that fulfilled the definition of acute infections during follow-up were also excluded [ 18 ].…”
Section: Methodsmentioning
confidence: 99%